Aliiroseovarius marinus sp. nov., isolated from seawater. Issue 1 (3rd February 2020) - Wang, Yan; Zhang, Yao; Guo, Changjiang; Liu, Tingwei; Dai, Yuanchen; Lin, Ming; Cui, Caixia; Zhang, Yuyang; Zhou, Chenyan; Zhu, Wuling
Abstract : A novel Gram-stain-negative, rod-shaped, non-spore-forming, non-flagellated, strictly aerobic strain, designated A6024 T, was isolated from coastal seawater near Rizhao, PR China (119.61° E 35.47° N). The organism grew optimally at 28 °C, in pH 6.0–7.0 and in the presence of 3.0 % (w/v) NaCl. The strain required seawater or artificial seawater for growth and NaCl alone did not support growth. Strain A6024 T contained ubiquinone 10 as the sole respiratory quinone and C18 : 1 ω 7 c (75.2 %) as the most abundant fatty acid. The predominant polar lipids were phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, phosphatidylcholine, one unidentified aminolipid and two unidentified lipids. The DNA G+C content of strain A6024 T was 59.9 mol%. The results of phylogenetic analysis based on 16S rRNA gene sequences showed that the novel strain was related most closely to Aliiroseovarius halocynthiae MA1-10 T, Aliiroseovarius pelagivivens GYSW-22 T and Aliiroseovarius crassostreae CV919-312 T with 98.3, 97.6 and 97.4 % sequence similarities, respectively. The calculated average nucleotide identity values and DNA–DNA hybridization values between strain A6024 T and the phylogenetically related Aliiroseovarius species were in the range 76.0–85.6 % and 19.6–29.4 %,  respectively. On the basis of the results of polyphasic analyses, strain A6024 T represents a novel species of the genus Aliiroseovarius, for which the name Aliiroseovarius marinus sp. nov. is proposed. The type strain is A6024 T (=KCTC 72114 T =MCCC 1K03595 T ).